Organoleptic and nutritional quality evaluation of jackfruit bulbs preserved in sugar syrup - Maheswari, T Uma; Valsan, Vidhu; Padmanaban , J (Journal of Postharvest Technology, 2024)
The experiment was conducted in a completely randomized design with jackfruit bulbs preserved in four formulations with variations in sugar  concentration and five replications (T1- 89 %, T2-76 %, T3- 63 %, T4-50 %). The effect of the processing on the nutritional quality and sensory  quality, storage life and cost economics was also calculated in this study. The sensory evaluation was carried out monthly for a period of six  months during storage. Results revealed that, the bulbs preserved in 89 % sugar syrup(T1) was considered as the best treatment when  compared to others with an ascorbic acid content of 3.64 mg/100g, carotenoids of 4.23 mg/100g and fat content of 2.32 g. Treatment T1 observed as a sample with maximum shelf life period of five months. The average sensory scores for taste (8.6), colour (8.4), flavour (8.4)  and overall acceptability (8.6) of jackfruit bulbs preserved in sugar syrup was initially maximum in T1 formulated with 89% of sugar  concentration. The same trend was maintained in all months of evaluation with gradual reduction in scores. Cost of production of bulbs  preserved in sugar syrup was estimated with the benefit cost ratio of 1.49.
Keywords: Jackfruit bulbs; preservation; sugar syrup